Employment success of social assistance recipients: A provincial analysis by industry. (1st February 2023) - Draghici, Elena; Holm, Anders; Haan, Michael
Abstract: Poverty continues to burden millions of Canadians each year, and social assistance (SA) is one program that provides last‐resort financial assistance, conditional upon looking for and accepting work. Using tax panel data of SA recipients from across seven Canadian regions between 2000 and 2018, we model the probabilities of employment success (ES) across industry of employment, SA benefit amounts, unionization, and individual‐level characteristics. We adopt an economic stance to explain reliance upon SA, examining the broader macroeconomic indicators of ES, and to demonstrate the factors associated with exiting SA. We find that many SA recipients do not present evidence of recent employment, indicating a disconnect between stated SA program aims and their outcomes. We provide evidence for increased SA benefits and unionization as significant predictors of ES of SA recipients. Résumé: La pauvreté continue de peser sur des millions de Canadiens chaque année, et l'aide sociale (AS) est un programme qui fournit une aide financière de dernier recours, à condition de chercher et d'accepter un emploi. À l'aide de données fiscales de panel sur les bénéficiaires de l'aide sociale de sept régions canadiennes entre 2000 et 2018, nous modélisons les probabilités de réussite professionnelle en fonction du secteur d'emploi, du montant des prestations d'aide sociale, de la syndicalisation et des caractéristiques individuelles. Nous adoptons une position économique pour expliquer le recours à l'AS, en examinant les indicateurs macroéconomiques plus larges de la réussite professionnelle, et pour démontrer les facteurs associés à la sortie de l'AS. Nous constatons que de nombreux bénéficiaires de l'AS ne présentent pas de preuve d'emploi récent, ce qui indique un décalage entre les objectifs déclarés du programme d'AS et leurs résultats. Nous fournissons des preuves que l'augmentation des prestations d'AS et la syndicalisation sont des prédicteurs importants de la réussite de l'emploi des bénéficiaires de l'AS.